How Great is thy Dictionary? Cross-referencing as a Lexicographic Device in The Greater Dictionary of (isi)Xhosa - Nkomo, Dion; Nosilela, Bulelwa; Gambushe, Wanga (Lexikos, 2022)
Inspired by Willem Botha’s reflections on the compilation of the multi-volume Woordeboek van die Afrikaanse Taal (WAT) in Botha (1994; 2005), this study offers a critical evaluation of cross-referencing in The Greater Dictionary of (isi)Xhosa, henceforth the GDX. The GDX is a tri-volume dictionary, possibly the biggest dictionary, not only in isiXhosa, but in African languages. The evaluation of the dictionary is guided by the notion of cross-reference conditions or cross-reference prerequisites to identify cross-references used in the GDX, analyse the relations revealed by cross-referencing and the effectiveness of the entire mediostructural organisation of the dictionary. The article notes that cross-referencing in the GDX seems to be guided by a generally well-conceived set of guidelines which were largely followed meticulously. Consistency generally prevails in the treatment of similar lexical items and even across the different volumes of the dictionary. Some cross-referencing aspects that could be improved were identified. However, it was noted that most of them would be easily addressed in the prospective digitisation project of the GDX. Keywords: cross-reference, cross-referencing, cross-reference conditions, cross-reference prerequisites, data distribution structure, dictionary structure, isiXhosa lexicography, mediostructure